PATRONAZH SERVICE OF AGED PEOPLE AS A CURRENT OBJECT OF STATISTICAL RESEARCH - L. A. Davletshina; M. V. Karmanov (Вестник университета)
Presently, the noticeable growth of number of the persons of old age suffering from the most various diseases has been turned into a serious problem, both for separate families, and for the state in general, seeking to provide sustainable social and economic development at the federal and regional levels. In this regard the great scientific and practical value acquires patronage as the modern instrument of support and providing aged. Improvement of methodology of a comprehensive statistical investigation of scales, prevalence and results of activity of patronage service plays an important role for its development, especially in the context of development of the system of indicators for complex assessment of so specific public phenomenon.